2015
DOI: 10.1001/jamaophthalmol.2014.4498
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Aspects of Usher Syndrome and theUSH2AGene in a Cohort of 433 Patients

Abstract: IMPORTANCE A new statistical approach is needed to describe the clinical differences between type I and type II Usher syndrome and between the 2 most frequent mutations in the USH2A gene. OBJECTIVES To describe the primary phenotypic characteristics and differences between type I and type II Usher syndrome and to establish a phenotype-genotype correlation for the 2 most frequent mutations in the USH2A gene. DESIGN, SETTING, AND PARTICIPANTS Cross-sectional study at a genetics department, in which clinical eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
63
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 44 publications
4
63
0
5
Order By: Relevance
“…Mex RD1 had compound heterozygous mutations; a novel nonsense variant c.10820A>C (p.His3607Pro) and a previously reported mutation c. 11864G>A (p.Trp3955*) (25). A previously reported homozygous USH2A mutation c. 2276G>T (p.Cys759Phe) was observed in the Mex RD101 pedigree (Table 1)(26, 27). Neither of the two affected siblings of Mex RD1 (Fig 1B) had sensorineural hearing loss.…”
Section: Resultsmentioning
confidence: 85%
“…Mex RD1 had compound heterozygous mutations; a novel nonsense variant c.10820A>C (p.His3607Pro) and a previously reported mutation c. 11864G>A (p.Trp3955*) (25). A previously reported homozygous USH2A mutation c. 2276G>T (p.Cys759Phe) was observed in the Mex RD101 pedigree (Table 1)(26, 27). Neither of the two affected siblings of Mex RD1 (Fig 1B) had sensorineural hearing loss.…”
Section: Resultsmentioning
confidence: 85%
“…Notably, mutations in USH2A could lead to Usher syndrome or RP. 21 In this study, patient F1:II:2 was clinically diagnosed to suffer from RP. Our data also provide novel genotype-phenotype correlations in cases of IRDs.…”
Section: Discussionmentioning
confidence: 89%
“…Diverse audiological phenotypes from mild to profound hearing loss have been reported in USH2A variants [18,19,31], although most patients exhibited a moderate degree of hearing loss. By reporting two novel variants of USH2A, our findings provide novel insights regarding the expansion of audiological spectrum from moderate to severe SNHL to more than severe SNHL in Koreans, supporting the diverse auditory phenotype of USH2.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has recently been suggested that there is evidence of genotype-phenotype correlation for some known USH2A variants. In detail, based on a large cohort study evaluating patients diagnosed with USH, most carriers of p.Glu767Serfs*21 variant showed moderate deafness, whereas patients with p. Cys759Phe variant exhibited only mild hearing loss [31]. Furthermore, a recent study suggested that an alternative allele may contribute to the variation in auditory manifestation [18].…”
Section: Discussionmentioning
confidence: 99%